Characterization of Silane Modified Polyvinyl Acetate Water Based Dispersion Film - Dubininkas, Mindaugas; Buika, Gintaras (Journal of Research Updates in Polymer Science, 2015)
Major advantage of silane-modified systems is possibility to cross link reactive silanol groups and fortify polymer mechanical and chemical properties. However, application of modern analysis techniques and further characterization of macromolecular structure produced is complicated due to a poor solubility of silane modified polymer in various solvents. Silane modified polyvinyl acetate (PVAc) dispersions were produced by classic radical and RAFT polymerization using silane co-monomers and dispersion system stabilizer - silane modified industrial grade polyvinyl alcohol. The present paper deals with confirmation of silanol, siloxane bonds, silicon content and distribution, as well film surface morphology of silane modified PVAc dispersions films.